KATURANGGAN WANITA MERUPAKAN SALAH SATU MEDIA TEKNOLOGI INFORMASI DAN KOMUNIKASI MASA LAMPAU - Wahjudhi Dwidjowinoto (Universitas PGRI Adi Buana Surabaya, 2018)
In looking at the character and characteristics of a woman who is good and not good or who is called Katuranggan as a marker of the basic character. Katuranggan comes from the word turangga which means horse. The science of katurangan is actually a science of the traits and traits of horses as the mounts as well as the train pullers. Furthermore, this term katuranggan borrowed/used also to understand the characteristics of women based on their physical characteristics. This paper discusses female customers based on those of Serat Centhini, the character of Arjuna's wives, female characters from the face, the female character based on the impression of their body, the female character based on the expression of the expression, the female character according to the characteristics of their body.